(untitled) (Philological Studies, 2019)
Starting from the house as a standardized category of culture (man-made edifice, home for the living, solid, immovable, safe, with an appropriate inner structure), the oral epics diverges from the standard by introducing the atypical attribution to it (dark house = a grave; cursed or strange house = dungeon; eternal house = gallows; God`s house = church etc.). Although along the corpus (of around 1500 songs) it is never named as house, the inn/tavern is a part of the same spatial system and encoded within the same logic: it is a human edifice, but built in the forest/mountain; it belongs to men, but its owner and keeper is a woman (quite exclusive for epics!); it is a humanly home, but of a temporary character. In addition, its encoding is double – it can be found both in the forest and in the town. In both cases it is a place of spatial discontinuity, a “weak spot” in space: an entrance to the other world (when in the forest/mountain) or the point of demonic breach into the protected world of an epic hero (to his city/hall/tower).